2009
DOI: 10.1002/iub.271
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear protein 1 induced by ATF4 in response to various stressors acts as a positive regulator on the transcriptional activation of ATF4

Abstract: SummaryNuclear protein 1 (NUPR1) was originally identified as p8, a member of the family of HMG-I/Y transcription factors induced in response to various cellular stressors. However, the signaling pathway underlying NUPR1 induction by cellular stresses remains to be established. In this study, we found that the expression of NUPR1 by various stresses induced by activating transcription factor 4 (ATF4). Loss of ATF4 using siRNA significantly diminished NUPR1 expression. Overexpression of ATF4 caused NUPR1 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Furthermore, silencing ATF4 using siRNA reduced transcription of CHOP, NUPR1 and PUMA, resulting in diminished apoptosis following treatment with encorafenib plus binimetinib. This is consistent with two reports showing that siRNA against ATF4 reduces NUPR1 expression and that ATF4-CHOP-mediated ER-stress causes neuronal apoptosis via PUMA induction (28,33). …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, silencing ATF4 using siRNA reduced transcription of CHOP, NUPR1 and PUMA, resulting in diminished apoptosis following treatment with encorafenib plus binimetinib. This is consistent with two reports showing that siRNA against ATF4 reduces NUPR1 expression and that ATF4-CHOP-mediated ER-stress causes neuronal apoptosis via PUMA induction (28,33). …”
Section: Discussionsupporting
confidence: 93%
“…Three of the highest expressed genes in terms of dominance from the data of this study (with significant up-regulation ) were identified as activating transcription factor 4 (Atf4) m RNA and two genes that are controlled by Atf4 which include 1) nuclear protein 1 (Nupr1) and 2) CHAC1 (cation transport regulator-like protein 1). Nuclear protein 1 is highly up-regulated in response to various stressors (Jin et al, 2009), playing a role in metastasis, progression of cancer and chemo-resistance in various types of malignancies. (Chowdhury et al, 2009) Nupr1 forms a complex with p53 and up-regulates p21, Bcl-x (L), allowing for cells to progress through cell cycle in presence of chemotherapy drugs.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Real-time PCR assays were conducted using QuantiTect SYBR Green PCR Kit (Qiagen, Valencia, CA, USA) on a Roche LightCycler 96 real-time PCR machine (Roche Diagnostics GmbH, Roche Applied Science, Penzberg, Germany). Primer sequences for real-time PCR were as follows: Bnip3 (5′-TTCAGCAATAATGGGAACGG-3′ and 5′-TGTT TCAGAAGCCCTGTTGG-3′; 180 bp product) and β-actin (5′-GGATTCCT ATGTGGGCGACGA-3′ and 5′-GAGTCCATCACGATGCCAGTG-3′; 315 bp product) (Jin et al, 2009). The protocol involved an initial 10-min denaturing step at 95°C, followed by 45 cycles of 95°C for 15 sec, 55°C for 30 sec, and 72°C for 30 sec.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA primed with oligo dT was prepared from 2 μg of total RNA using M-MLV reverse transcriptase (Invitrogen). The following specific primers were used for PCR: Bnip3 (5'-GATACCAACAGGGCTTCTGAAA CAG-3' and 5'-CAGAGAATATGCCCCCTTTCTTCA-3'; 253 bp product), Hif-1α (5′-CTCAAAGTCGGACAGCCTC-3′ and 5′-CCCTGCAGTAGGTTTC TGC-3′; 460 bp) (Leonard et al, 2003) and β-actin (5'-GGATTCCTATGT GGGCGACAG-3' and 5'-CGCTCGGTGAGGATCTTCATG-3'; 438 bp product) (Jin et al, 2009). PCR products were subjected to electrophoresis on 1.5% agarose gels and visualized with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%